2010
DOI: 10.1007/s00432-010-0762-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein biomarkers screening in HCC patients with liver cirrhosis by ICAT-LC-MS/MS

Abstract: cICAT combined with LC-MS/MS-based serum proteome analysis can be useful in the screening of serum biomarkers for HCC. Alpha-1-acid glycoprotein combining AFP could aid the diagnosis of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…Similar to previous reports (12,13), our study clearly shows the identified set of differentially overexpressed proteins, including serum amyloid A protein (SAA1), HP and sp40, between LC and HCC patients by 2-DE. They are all members of acute phase proteins (APPs) family, and most were responsible for liver-synthesized proteins.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to previous reports (12,13), our study clearly shows the identified set of differentially overexpressed proteins, including serum amyloid A protein (SAA1), HP and sp40, between LC and HCC patients by 2-DE. They are all members of acute phase proteins (APPs) family, and most were responsible for liver-synthesized proteins.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, sera from 27 HCC patients with hepatocellular carcinoma (HCC) and 10 LC ONCOLOGY REPORTS 24: 1271-1276, 2010 …”
Section: Methodsmentioning
confidence: 99%
“…One such method uses isotope coded affinity tags (ICATs), involving chemical labeling of isolated proteins and peptides by isobaric tags that facilitates comparison of the proteomes of two samples simultaneously [40]. While ICATs involve chemical modification of proteins to tag them before analysis by mass spectrometry, stable isotope labeling with amino acids in cell culture (SILAC) is a simple approach for in vivo incorporation of a label (specific amino acids) into proteins that avoids chemical manipulations.…”
Section: Technologies Involved In Proteomicsmentioning
confidence: 99%
“…AAt belongs to acute phase protein (APP) whose expression is significantly increased in inflammation, trauma, infection and tumorigenesis. Many studies have suggested that serum levels of App have a high clinical value in various cancer diseases including colorectal cancer (20), lung cancer (21), hepatoma (22), breast cancer (23) and others (24). Protein level of serum AAT was significantly increased during inflammation trauma, infection, and tumorigenesis (20), especially in lung cancer (21) and liver cancer (25).…”
Section: Discussionmentioning
confidence: 99%